Enrichment of Autophagy and Proteosome Pathways in Breast Muscle of Feed Efficient Pedigree Male Broilers - Piekarski-Welsher, Alissa; Greene, Elizabeth; Lassiter, Kentu; Kong, Byungwhi Caleb; Dridi, Sami; Bottje, Walter (Frontiers in Physiology, 2018)
Background: Feed efficiency (FE) is an important genetic trait in poultry and livestock. Autophagy (self-eating) and proteosomes are cellular processes that remove damaged cell components (e.g., proteins, organelles). As evidence of extensive protein oxidation was observed in Pedigree Male (PedM) broilers exhibiting a low FE (LFE) phenotype compared to a high FE (HFE) phenotype, the main goal of this study was to assess gene and protein expression of the autophagy and proteosome pathways in breast muscle obtained in PedM broilers exhibiting HFE and LFE phenotypes. Methods: Feed efficiency was calculated as weight gain divided by feed intake gain in individual PedM broilers that were measured between 6 and 7 weeks of age. Targeted gene expression was conducted on breast muscle using quantitative real-time polymerase chain reaction (qPCR) to determine mRNA expression of genes associated with the autophagy pathway; AMP-activated protein kinase alpha 1 (AMPKα1), mammalian target of rapamycin (mTOR), Beclin 1, and autophagy genes (Atg) 3, Atg7, and Atg16L1. Binomial distribution analysis was conducted on transcriptomic and data obtained by RNAseq and shotgun proteomics, respectively on the same set of tissues for genes associated with autophagy, vacuole formation, and proteosome expression. Results: Greater efficiency was attained in the HFE PedM broilers by greater weight gain on the same amount of feed consumed resulting in FEs of 0.65 ± 0.01 and 0.46 ± 0.01 in the HFE and LFE phenotypes, respectively. Targeted mRNA expression analysis revealed significant (P < 0.05) elevations in AMPKa1, mTOR, Atg16L1, and Atg7 and a marginal (P = 0.07) elevation in Beclin1. Binomial distribution analysis transcriptomic and proteomic data revealed significant skews favoring autophagy-, vacuole-, and proteosome-related genes in the HFE phenotype. These results indicate that the autophagy and proteosome expression is enhanced in the HFE compared to the LFE pedigree male broiler phenotype suggesting that protein and organelle quality control may be enhanced in high feed efficiency.